2019
DOI: 10.1016/j.chembiol.2019.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Compound Promiscuity to Identify Targetable Cysteines within the Kinome

Abstract: Highlights d Our study highlights a multi-targeted strategy to identify druggable cysteines d We identified 23 covalent kinase targets across multiple spatial locations d Nine of these have previously not been covalently targeted by an inhibitor d Our findings highlight potential means to advance covalent drug discovery efforts

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 79 publications
1
50
0
Order By: Relevance
“…In addition, the presence of accessible cysteine residues within the MKK7 ATP binding pocket opens also an opportunity for irreversible targeting strategy 34 , supported by previous observations of covalent binding the natural product 5Z-7-oxzeaenol and promiscuous aminopyrimidine SM1-71 with the kinase domain [35][36][37] . In addition, previous studies have demonstrated that ibrutinib which is an BTK inhibitor can interact covalently with MKK7 in cells 37,38 .…”
Section: Introductionmentioning
confidence: 71%
“…In addition, the presence of accessible cysteine residues within the MKK7 ATP binding pocket opens also an opportunity for irreversible targeting strategy 34 , supported by previous observations of covalent binding the natural product 5Z-7-oxzeaenol and promiscuous aminopyrimidine SM1-71 with the kinase domain [35][36][37] . In addition, previous studies have demonstrated that ibrutinib which is an BTK inhibitor can interact covalently with MKK7 in cells 37,38 .…”
Section: Introductionmentioning
confidence: 71%
“…By utilizing a multitargeted kinase inhibitor, SM1-71, that serves as an effective tool compound we were able to elucidate molecular mechanisms driving specific cancer cell types. In our previous study, we used SM1-71 to interrogate the human kinome to identify cysteines that can be targeted because of the covalent nature of the compound (45). In the present study, we extended the use of this compound to the investigation of signaling pathways that drive cellular proliferation in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…1a). We previously used chemical proteomic approaches to elucidate ϳ54 kinase targets of SM1-71 (45) (Table S1) and identified 24 kinases as exhibiting an IC 50 value Ͻ10 M ( Table 1). Thirteen of these kinases have well-annotated functions in promoting cell growth and proliferation, including YES1, SRC, MAP2K2 (MEK2), AURKA, MAP2K1 (MEK1), MAP3K1, MAPK1 (ERK2), MAPK3 (ERK1), WEE1, IGF1R, INSR, DDR1, and MET.…”
Section: Investigating the Cytotoxic Effect Of Sm1-71 Across Multiplementioning
confidence: 99%
See 2 more Smart Citations